Rare cutaneous metastases in advanced colon cancer: A case report - Santi, Santi; Septarendra, Denny (Edelweiss Applied Science and Technology, 2025)
Cutaneous metastases derived from colorectal tumors are rare, occurring in only 4% of cases of metastatic colorectal cancer. They are most often located on the abdominal skin. A 36-year-old male presented with lumps in his lower right quadrant abdomen two months ago. A previous abdominal CT scan revealed a mass in the ascending colon, but he rejected any medication and returned with total obstruction one month later, willing to take any action. We found an intraluminal cecal mass and a metastatic liver nodule, so we performed a right hemicolectomy and ostomy. One month after discharge, multiple nodules appeared on the patient’s face, chest, and abdominal skin, which were confirmed by FNAB to be metastatic adenocarcinoma. We planned an adjuvant chemotherapy FOLFIRI regimen. Commonly, advanced colorectal cancers have the highest rate of metastases to the liver, lungs, and bones. Cutaneous metastases derived from colorectal tumors are rare, occurring in only 4% of cases of metastatic colorectal cancer. Generally, cutaneous metastases appear several years after resection or diagnosis. In this case, the interval between definitive hemicolectomy and cutaneous metastases was two months, indicating a poor prognosis. Cutaneous metastases are a very rare manifestation of advanced colorectal cancer and indicate poor prognosis.